The effect of the strategy (rediscription) on the achievement of fifth-Class Pupils in science and collective thinking (Journal of the College of Basic Education, 2024)
The aim of the current research is to identify "the effect of the strategy (rediscription) on the achievement of fifth-grade female students in science and their collective thinking", through the following one null hypotheses:1- There is no statistically significant difference at the level (0.05) between the average scores of the experimental group students who were studied according to the strategy rediscription and the average scores of the control group students who were taught according to the usual method in the achievement test in science.The experimental design with two experimental and control groups, one of which controls the other partially, was chosen from the post-test for achievement and collective thinking, and the current research community is represented by the fifth grade students in the daytime government primary schools of the Al-Muthanna Education Directorate for the academic year (2022-2023), and it was chosen (Al-Yamamah Primary School for Girls) as a model to represent the research sample. It was distributed into two groups, an experimental and a control group, as the number of students in the experimental group was (34) students, and the number of students in the control group was (31) students.The two groups were rewarded in the variables (previous achievement, previous information, chronological age, intelligence, science processes), and the experiment was conducted in the first semester of the academic year (2022-2023).The researcher taught the students of the two groups by herself and identified the scientific material in the third units of the Taxt Book 5th Edition for the year 2021, the behavioral objectives of the cognitive domain were determined within the four levels of Bloom's classification of the cognitive domain. respectively (remembering, comprehending, applying) with a number of about (201) behavioral objectives, the researcher prepared (36) study plans according to the strategy (rediscription) for teaching the students of the experimental group and the same according to the usual method for teaching the students of the control group. A sample of it was presented to a group of arbitrators to see its validity and suitability for fifth-grade students.The researcher these has prepared: First: an achievement test of a multiple-choice type with three alternatives consisting of (30) items, according to Bloom's classification of the cognitive domain, then verify the (virtual) validity of the test by presenting it to a group of arbitrators in the field of methods of teaching science, psychological and educational sciences, measurement and evaluation, and the validity of the content By preparing the test map (the specification table) and calculating stability by the half-partition method using Kewder-Richardson equation 20, the correlation coefficient reached (0.87).The researcher applied the two research tools to the main sample after the end of the experiment period, which lasted (14) weeks, during which the researcher studied the students of the two research groups by herself, and after analyzing the results statistically using the t-test for two independent samples (for the achievement test), the results resulted in superiority The experimental group that studied according to the strategy (rediscription) on the control group that studied in the usual way in the achievement test and, based on the results of the research, the researcher concluded that:. The adoption of the rediscription strategy in teaching contributed to raise the level of academic achievement in science for the fifth grade of primary school.In the light of the results, the researcher concluded that teaching with the strategy rediscription has an impact on the students' achievement in science which was with an(0,87) estimate (high) for the two variables on the straight.Accordingly, the researcher presented a number of recommendations and suggestions